MGWAS Uncovers Gln-Glucosinolate Seed-Specific Interaction and its Role in Metabolic Homeostasis. Issue 2 (21st April 2020) - Slaten, Marianne L.; Yobi, Abou; Bagaza, Clement; Chan, Yen On; Shrestha, Vivek; Holden, Samuel; Katz, Ella; Kanstrup, Christa; Lipka, Alexander E.; Kliebenstein, Daniel J.; Nour-Eldin, Hussam Hassan; Angelovici, Ruthie
Abstract : mGWAS of Gln-related traits reveals an unexpected seed-specific interaction between glutamine and glucosinolates and in shaping the metabolic homeostasis in Arabidopsis seeds. Abstract: Gln is a key player in plant metabolism. It is one of the major free amino acids that is transported into the developing seed and is central for nitrogen metabolism. However, Gln natural variation and its regulation and interaction with other metabolic processes in seeds remain poorly understood. To investigate the latter, we performed a metabolic genome-wide association study (mGWAS) of Gln-related traits measured from the dry seeds of the Arabidopsis ( Arabidopsis thaliana ) diversity panel using all potential ratios between Gln and the other members of the Glu family as traits. This semicombinatorial approach yielded multiple candidate genes that, upon further analysis, revealed an unexpected association between the aliphatic glucosinolates (GLS) and the Gln-related traits. This finding was confirmed by an independent quantitative trait loci mapping and statistical analysis of the relationships between the Gln-related traits and the presence of specific GLS in seeds. Moreover, an analysis of Arabidopsis mutants lacking GLS showed an extensive seed-specific impact on Gln levels and composition that manifested early in seed development. The elimination of GLS in seeds was associated with a large effect on seed nitrogen and sulfur homeostasis, which conceivably led to the Gln response. This finding indicates that both Gln and GLS play key roles in shaping the seed metabolic homeostasis. It also implies that select secondary metabolites might have key functions in primary seed metabolism. Finally, our study shows that an mGWAS performed on dry seeds can uncover key metabolic interactions that occur early in seed development.